Retail pricing format and rigidity of regular prices - Sourav Ray; Avichai Snir; Daniel C. Levy (Bar-Ilan University, Department of Economics, 2021)
We study different notions of sale and regular prices, and their variability with store pricing-formats. We use data from three large stores with different pricing-formats (EDLP/Hi-Lo/Hybrid) that are located within 1-km radius. Importantly, the data contain both the actual transaction prices and the actual regular prices as displayed on the store shelves. We combine these data with two 'generated' regular price series and study their rigidity. Regular-price rigidity varies with store-formats because different format stores define regular-prices differently. Correspondingly, the meaning of price-cuts varies across store-formats. To interpret the findings, we consider the store pricing format distribution across the US.
Keywords: E31; 330; Price Rigidity; Sticky Prices; Regular Prices; Sale Prices; Filtered Prices; Reference Prices; Transaction Prices; Price Cuts; Pricing Format; Every Day Low Price (EDLP); Hi-Lo; Hybrid